2011
DOI: 10.1007/s00408-011-9306-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences on Pulmonary Function: A Large Sample Twin Study

Abstract: Heritability of forced expiratory volume in one second (FEV1), forced vital capacity (FVC), and peak expiratory flow (PEF) has not been previously addressed in large twin studies. We evaluated the genetic contribution to individual differences observed in FEV1FVC, and PEF using data from the largest population-based twin study on spirometry. Specially trained lay interviewers with previous experience in spirometric measurements tested 4,314 Danish twins (individuals), 46–68 years of age, in their homes using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
26
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 23 publications
8
26
1
Order By: Relevance
“…Our findings on the heritability of lung function are also in line with those previously reported (12,32,33). In the current sample, additive genetic factors accounted for 65% of the variability in FEV 1 and 67% of FVC.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings on the heritability of lung function are also in line with those previously reported (12,32,33). In the current sample, additive genetic factors accounted for 65% of the variability in FEV 1 and 67% of FVC.…”
Section: Discussionsupporting
confidence: 92%
“…In the current sample, additive genetic factors accounted for 65% of the variability in FEV 1 and 67% of FVC. Very similar heritability estimates of 61% and 67% for FEV 1 in older twins have been reported earlier (12,34). In addition, our estimate of the genetic contribution to FVC is comparable with the estimate (68%) reported by Tarnoki et al (32) and slightly higher than that (55%) reported by Ingebrigtsen and co-workers (12).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations